Improving Front Roll Learning Outcomes Using Inclusion Teaching Style Assisted by Gadget Media for Self Assessment in Grade 8 of Junior High School - Indriani, Maslina; Mashud, Mashud (STKIP PGRI Trenggalek, 2026)
This research aims to improve forward roll learning outcomes through the implementation of an inclusive teaching style assisted by gadget-based self-assessment. Adopting the Kemmis and McTaggart model, this Classroom Action Research was conducted in two cycles involving 31 eighth-grade students (Class 8B) at SMPN 1 Tabalong. Data were collected through psychomotor skill observations, affective assessments, and structured self-assessment sheets completed via gadgets after the students independently evaluated their recorded movements across five task-card difficulty levels. The findings revealed a substantial improvement. In the pre-cycle stage, classical mastery was 0%, with an average psychomotor score of 36.7. Following the intervention in Cycle I, mastery increased to 67.7% with an average score of 74.5. By Cycle II, classical mastery reached 100% with an average psychomotor score of 85.4 and a maximum affective score of 100. Furthermore, the quality of instructional delivery by the teacher improved from the 'Good' to the 'Very Good' category. In conclusion, integrating an inclusive teaching style with gadget-assisted self-assessment effectively enhances students' forward roll learning outcomes within the specific context of this study.